The Great Virtues, Objectives, and Contemporary Perspectives of Hijrah: An Analytical Study in the Light of Seerah Tayyibah - Sidra Nawaz; Munazza shahab; Asma Noreen (Journal of Religion and Society, 2026)
Migration (Hijrah) occupies a central and transformative place in Islamic thought, symbolizing not merely a physical relocation but a profound moral, spiritual, and intellectual transition. This study explores the عظیم فضائل (great virtues), مقاصد (objectives), and contemporary interpretations of Hijrah in the light of Seerah Tayyibah (the noble life of Prophet Muhammad ﷺ). The research argues that Hijrah represents a dynamic paradigm of sacrifice, resilience, faith, and socio-political reform, which continues to inspire Muslim societies in modern contexts. Drawing upon classical sources of Seerah, this analytical study examines the multidimensional purposes of Hijrah, including the preservation of faith, establishment of justice, formation of a cohesive community (Ummah), and the creation of an ethical socio-political order. The migration from Makkah to Madinah is analyzed as a strategic and divinely guided movement that laid the foundation for an Islamic civilization based on equality, brotherhood, and rule of law. Furthermore, the study highlights the spiritual excellence (fada’il) associated with Hijrah, such as sincerity (ikhlas), trust in Allah (tawakkul), and unwavering commitment to truth. In the context of modern thought, the concept of Hijrah is reinterpreted beyond its historical framework to address contemporary challenges. It is examined as a metaphor for personal transformation, intellectual migration from ignorance to knowledge, and ethical resistance against injustice and moral decline. The research also engages with current academic discourse, exploring how Hijrah can inform debates on identity, globalization, migration, and cultural integration in the modern world. By integrating classical Islamic teachings with contemporary perspectives, this study demonstrates that Hijrah remains a timeless and universal concept with enduring relevance. It not only provides guidance for spiritual growth but also offers a framework for social reform and intellectual renewal in an ever-changing global landscape. Keywords: Hijrah, Seerah Tayyibah, Migration in Islam, Spiritual Transformation, Islamic Civilization, Contemporary Thought, Moral Reform, Ummah, Tawakkul, Ikhlas